The Influence Of Flashcard Media On The Ability To Read Hijaiyah Letters Of 5-6 Year Old Children - Ela Fitri Dwiriani; Maryamah, Maryamah; Fitri, Izza (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2025)
This study is based on the background before the application of flashcard media found by researchers regarding the ability to read hijaiyah letters of children is less than optimal in utilizing educational game media, on indicators of the ability to read hijaiyah letter recognition, mention letter symbols, and oral pronunciation. The purpose of this study was to determine the effect of flashcard media on the ability to read hijaiyah letters for children aged 5-6 years at TK kemala bhayangkari 1 Palembang. This type of research is quantitative with the Pre-Experimental Design experiment research method. This research design uses One Group Pretest - Posttest Design. The population of this study were children in group B 1, totaling 25 children and sampling using purposive sampling to obtain samples that represented the objectives of the research conducted and had sample selection criteria at TK Kemala Bhayangkari 1 Palembang. Data collection techniques used observation, tests, and documentation. The data analysis technique in this study used validity test, reliability test, normality test, homogeneity test, and t hypothesis test. The results of this study before the application of flashcard media the ability to read hijaiyah letters is less than optimal in the use of educational media, after the flashcard media has increased, it can be seen from the assessment results that the significance value is 0.00 (<0, 05) then H0 is rejected, meaning that there is an influence of flashcard media on the ability to read hijaiyah letters for children aged 5-6 know. Which means that there is a significant effect of flashcard media on the ability to read hijaiyah letters for children aged 5-6 years in Kemala Bhayangkari 1 Palembang kindergarten.